2009
DOI: 10.1002/dvdy.22112
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of cardiac progenitor cells and their derivatives in the embryonic heart post‐chamber formation

Abstract: There is scant information on the fate of cardiac progenitor cells (CPC) in the embryonic heart after chamber specification. Here we simultaneously tracked three lineage-specific markers (Nkx2.5, MLC2v, and ANF) and confirmed that CPCs with an Nkx2.5 1 MLC2v 2 ANF 2 phenotype are present in the embryonic (E) day 11.5 mouse ventricular myocardium. We demonstrated that these CPCs could give rise to working cardiomyocytes and conduction system cells. Using a two-photon imaging analysis, we found that the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
(80 reference statements)
4
15
0
Order By: Relevance
“…These findings confirmed the MS results in which 3 peptides were exclusively identified only in medium of NRVMs: 2 peptides covering a part of ANP prohormone sequence and 1 peptide matching the partial sequence of ANP hormone [17]. ANP is considered to be a cardiac lineage marker as it is expressed early during the differentiation of myocytes [85] and early during heart development [86]. This suggests that since CSCs are like embryonic and other progenitor cells [87], they do not secrete ANP but they would during differentiation into cardiac myocytes.…”
Section: Secretome Proteomicssupporting
confidence: 77%
“…These findings confirmed the MS results in which 3 peptides were exclusively identified only in medium of NRVMs: 2 peptides covering a part of ANP prohormone sequence and 1 peptide matching the partial sequence of ANP hormone [17]. ANP is considered to be a cardiac lineage marker as it is expressed early during the differentiation of myocytes [85] and early during heart development [86]. This suggests that since CSCs are like embryonic and other progenitor cells [87], they do not secrete ANP but they would during differentiation into cardiac myocytes.…”
Section: Secretome Proteomicssupporting
confidence: 77%
“…7, A-C) since previously we demonstrated that Nkx2.5 ϩ /MF20 Ϫ cells differentiate into MF20 ϩ expressing cardiomyocytes in vitro (30). Conversely, cells positive for both ␤-Gal and MF20 (␤-Gal ϩ /MF20 ϩ ) were considered to be cardiomyocytes (Fig.…”
Section: E115 Ventricular Cells and Gets Cleaved Into Its Biologicalmentioning
confidence: 84%
“…Although NPRA mRNA expression is the lowest at E11.5 stage, we have chosen to study the effects of ANP on ventricular cells from this stage. This is primarily due to the fact that CPCs are abundant in E11.5 ventricular myocardium and their numbers decline precipitously at later developmental stages (30,47,48). While NPRA mRNA levels are lowest at E11.5 stage, Western blot analyses indicate that NPRA protein levels at E11.5 are comparable to later developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…Ten-micrometer cryosections were obtained from the adult hearts and processed for visualization of fibrosis by Picro Sirius Red (Direct Red 80 CI 35780; Sigma) and Fast Green (FCF CI 42053; Fisher) (PSFG) staining as described earlier (14,15). Cryosections or cultured cells were incubated with primary antibodies for CDK1 (sc-954; Santa Cruz Biotechnology, Santa Cruz, CA), sarcomeric myosin [MF-20; Developmental Studies Hybridoma Bank (DSHB), University of Iowa], von Willebrand factor (sc-14014), DDR2 (sc-8989), and ␣-smooth muscle actin (1E12-s; DSHB), followed by anti-rabbit and or anti-mouse secondary antibodies conjugated to Alexafluor 488 and 555 (Invitrogen) as described in our earlier publications (36,52,56). The samples were examined using a Leica DM2500 epifluorescence microscope fitted with Leica DFC500 digital acquisition system.…”
Section: Methodsmentioning
confidence: 99%
“…Media were changed after 1 h to eliminate unattached or weakly adherent cells such as cardiomyocytes and endothelial cells. Embryonic day 15.5 (E15.5) primary cultures composed of ventricular myocytes and fibroblasts were generated as described earlier (36,52). In brief, female CD1 mice were time-mated to obtain E15.5 embryos.…”
Section: Methodsmentioning
confidence: 99%